Toxoplasma gondii: cloning, sequencing, expression, and antigenic characterization of ROP2, GRA5 and GRA7 - Igarashi, M.; Kano, F.; Tamekuni, K.; Kawasaki, P. M.; Navarro, I. T.; Vidotto, O.; Vidotto, M. C.; Machado, R. Z. [UNESP]; Garcia, J. L. (Funpec-editora, 2008)
Toxoplasma gondii is an intracellular obligate protozoan, which infects humans and warm-blooded animals. The aim of the present study was to clone the rop2, gra5 and gra7 genes from T. gondii RH strain and to produce recombinant proteins. The rop2, gra5 and gra7 gene fragments produced by polymerase chain reaction were cloned into the pET102/D-TOPO(R) vector which contains thioredoxin and polyhistidine tags at the C-and N-ends, respectively, and is expressed in Escherichia coli BL21(DE-3). The expression fusion proteins were found almost entirely in the insoluble form in the cell lysate. These recombinant proteins were purified with an Ni-NTA column. Concentrations of the recombinant antigens produced in the E. coli BL21-star ranged from 300 to 500 mu g/mL growth media, which was used to immunize rabbits. We observed an identity ranging from 96 to 97% when nucleotide sequences were compared to GenBank database sequences. Immunocharacterization of proteins was made by indirect immunofluorescence assay. These proteins will be used for serodiagnosis and vaccination.
Keywords: Toxoplasma gondii; ROP2; GRA5; GRA7; Cloning; expression; antigenic characterization